A class of relativistic anisotropic charged stellar models in isotropic coordinates - Pant, Neeraj; Pradhan, Nirakar; Murad, Mohammad Hassan (© 2014, Springer Science+Business Media Dordrecht., 2016)
This article was published in the Journal of Astrophysics and Space Science [© 2014, Springer Science+Business Media Dordrecht.] and the definite version is available at : http://dx.doi.org/10.1007/s10509-014-2156-8. The Journal's website is at: http://link.springer.com/article/10.1007%2Fs10509-014-2156-8